2009
DOI: 10.3892/ijo_00000235
|View full text |Cite
|
Sign up to set email alerts
|

CYP1B1, but not CYP1A1, is downregulated by promoter methylation in colorectal cancers

Abstract: Abstract. Cytochrome P450 (CYP) 1A1 (CYP1A1) and CYP1B1, dioxin-inducible CYP1s, are associated with carcinogenesis in extrahepatic tissues. CYP1B1 is featured in carcinogenesis of hormone-responsive tissues, where the CYP1B1 level is considerably high. Although aberrant expression of these enzymes is also observed in cancers that are not related to hormone response, their roles in carcinogenesis are not yet fully understood. We examined DNA methylation status of the CpG islands within the 5'-flanking region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
0
31
0
2
Order By: Relevance
“…It is well established that methylation of cytosine residues of genomic DNA (DNA methylation) of the regulatory region(s) of a gene can lead to silencing or diminished expression of the gene. Of particular interest, the promoter of the CYP1B1 gene exhibits DNA methylation in a portion of colorectal (Habano et al, 2009) and gastric (Kang et al, 2008) cancers. Studies conducted in our laboratory demonstrated the mechanisms through which DNA methylation causes CYP1B1 silencing and also shed light on the mechanisms of gene regulation in mammalian cells in general (Beedanagari et al, 2010a).…”
Section: Role Of Epigenetic Mechanisms In Differential Regulation Of mentioning
confidence: 99%
“…It is well established that methylation of cytosine residues of genomic DNA (DNA methylation) of the regulatory region(s) of a gene can lead to silencing or diminished expression of the gene. Of particular interest, the promoter of the CYP1B1 gene exhibits DNA methylation in a portion of colorectal (Habano et al, 2009) and gastric (Kang et al, 2008) cancers. Studies conducted in our laboratory demonstrated the mechanisms through which DNA methylation causes CYP1B1 silencing and also shed light on the mechanisms of gene regulation in mammalian cells in general (Beedanagari et al, 2010a).…”
Section: Role Of Epigenetic Mechanisms In Differential Regulation Of mentioning
confidence: 99%
“…It is noteworthy that in a portion of colorectal cancers, CpG dinucleotides at the CYP1B1 promoter are fully methylated, whereas CpG dinucleotides at the enhancer are only partially methylated, just as we observed with HepG2 cells (Habano et al, 2009). Our studies are therefore potentially relevant to the development of these cancers and provide insights into the mechanism of CYP1B1 induction and into the regulation of gene expression in mammalian cells in general.…”
Section: Discussionmentioning
confidence: 59%
“…Of considerable importance are the observations that the CYP1B1 promoter exhibits DNA methylation in a portion of colorectal (Habano et al, 2009) and gastric (Kang et al, 2008) cancers. It is noteworthy that in a portion of colorectal cancers, CpG dinucleotides at the CYP1B1 promoter are fully methylated, whereas CpG dinucleotides at the enhancer are only partially methylated, just as we observed with HepG2 cells (Habano et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP1B1 promoter methylation is downregulated in colorectal cancer (14) and stratifies prognosis in patients with tamoxifen-and non tamoxifen-treated breast cancer (15). The results demonstrated that CYP1B1 promoter methylation changed following treatment with various chemotherapy regimens, indicating complex regulation of CYP1B1 methylation in the bone marrow.…”
Section: Discussionmentioning
confidence: 91%